Evaluation of trace elements mobility from soils to sediments between the Iberian pyrite belt and the Atlantic Ocean - Batista, M.J. (2012)
An environmental study was conducted in 193 stream sediments and 355 soil samples collected in the lower section of Guadiana River Basin to evaluate the trace elements transfer from one compartment into another. The objective was to evaluate the dispersion of Pb, Cu, Zn and other chemical elements resulting from upstream mines into the lower N-S sector of the Guadiana River Basin to the Atlantic Ocean. The area partly includes the Iberian Pyrite Belt, a known volcanogenic massive sulphide (VMS) province with important mining activity history. Median concentrations of the elements Cu, Pb, Zn, Al, As, Ba, Br, Ca, Mg, Mn and Na are generally higher in the studied sediments than in soils. Soils are normally acidic and mobility of elements is in these conditions higher. When the relations between upstream soils and downstream sediments were established, median values were higher in the upstream soils only for elements such as Co, Ni, K, Pb, Mn and Ti, probably the less mobile, and the Cu, Zn, Al, As, Ba, Br, Ca, Cr, Fe, Mg and Na have highest concentrations in the downstream sediments. Lead was considered the less mobile element and Zn the highly mobile of the base metals in the mining area of the lower Guadiana River. Dispersion of the metals, considering the studied soil and sediment samples is partially restricted to the mining areas or downstream sediments but close to the mine sources, where ore tailings and acid waters occur. Near the mouth, concentrations of As, Cu, Pb and Zn increase in relation with mining and other pollution sources. Interaction with salt water forces chemical elements precipitation from water and subsequent increase of their concentration in sediments. This may be the reason for the increase of those chemical elements concentrations in the sediments